2001
DOI: 10.1046/j.1471-4159.2001.00655.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic O‐glycosylation is abundant in nerve terminals

Abstract: Phosphorylation plays a key role in regulating growth cone migration and protein traf®cking in nerve terminals. Here we show that nerve terminal proteins contain another abundant post-translational modi®cation: b-N-acetylglucosamine linked to hydroxyls of serines or threonines (O-GlcNAc 1 ). O-GlcNAc modi®cations are essential for embryogenesis and mounting evidence suggests that O-GlcNAc is a regulatory modi®cation that affects many phosphorylated proteins. We show that the activity and expression of O-GlcNAc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
127
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 184 publications
(130 citation statements)
references
References 73 publications
2
127
0
1
Order By: Relevance
“…The unfractionated rat brain homogenate contained both of these species, as well as a third major UCH-L1 species, which may be phosphorylated and/or O-glycosylated ( Fig. 1 Biii) (20). These 3 forms of UCH-L1 also were found in cell lysates from human neuroblastoma SH-SY5Y cells (Fig.…”
Section: A Subpopulation Of Uch-l1 (Uch-l1 M ) Is Tightly Bound To Mementioning
confidence: 88%
See 1 more Smart Citation
“…The unfractionated rat brain homogenate contained both of these species, as well as a third major UCH-L1 species, which may be phosphorylated and/or O-glycosylated ( Fig. 1 Biii) (20). These 3 forms of UCH-L1 also were found in cell lysates from human neuroblastoma SH-SY5Y cells (Fig.…”
Section: A Subpopulation Of Uch-l1 (Uch-l1 M ) Is Tightly Bound To Mementioning
confidence: 88%
“…The study reported here was initiated to identify posttranslational modifications of UCH-L1 that distinguish it from its widely expressed homolog UCH-L3 and that may be critical for its in vivo activity. UCH-L1 is O-glycosylated (20) and monoubiquitinated (21). We report here an additional modification that may significantly have an impact on its enzymatic and/or binding activities: UCH-L1 is farnesylated and associated with neuronal membranes, including the endoplasmic reticulum.…”
mentioning
confidence: 86%
“…The association between OGT and PP1 is particularly intriguing, as it may provide a direct mechanism to couple O-GlcNAc glycosylation to dephosphorylation of specific substrates. Although OGT is found in the nucleus, cytosol and mitochondria, it is particularly enriched in the nucleus 15 and the soluble synaptic compartment 16 .…”
Section: The Enzymes Ogt and Ogamentioning
confidence: 99%
“…Like OGT, OGA seems to be highly active at neuronal synapses 16 , and it is also found in the nucleus and cytosol 30 . OGA contains an N-terminal glycosidase domain and a putative Cterminal histone acetyltransferase (HAT) domain 31 .…”
Section: The Enzymes Ogt and Ogamentioning
confidence: 99%
See 1 more Smart Citation